2010
DOI: 10.1063/1.3408899
|View full text |Cite
|
Sign up to set email alerts
|

Three-terminal field effect devices utilizing thin film vanadium oxide as the channel layer

Abstract: Electrostatic control of the metal-insulator transition (MIT) in an oxide

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
114
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 29 publications
(59 reference statements)
0
114
0
Order By: Relevance
“…Thanks to the improvements in the quality of VO 2 thin films, there has been a growing emphasis on exploring logic and memory device applications of this intriguing phenomenon. Recent efforts on a Mott field effect transistor (MottFET) have demonstrated that VO 2 can be employed as the channel in a MottFET, and the applied external gate voltage switches the channel resistance between the insulating OFF state and the metallic ON state [4][5][6] . There are still several challenges for these so called "Mott devices" 7 , among which is a concern over the repeatability/reproducibility of the Mott transition because the properties of these materials are sensitive to oxygen vacancy concentration, strain, and other factors.…”
mentioning
confidence: 99%
“…Thanks to the improvements in the quality of VO 2 thin films, there has been a growing emphasis on exploring logic and memory device applications of this intriguing phenomenon. Recent efforts on a Mott field effect transistor (MottFET) have demonstrated that VO 2 can be employed as the channel in a MottFET, and the applied external gate voltage switches the channel resistance between the insulating OFF state and the metallic ON state [4][5][6] . There are still several challenges for these so called "Mott devices" 7 , among which is a concern over the repeatability/reproducibility of the Mott transition because the properties of these materials are sensitive to oxygen vacancy concentration, strain, and other factors.…”
mentioning
confidence: 99%
“…The R/R 0 increased again with applying V G = 100 V. The origin of such a slow resistance decrease is sometimes related to mechanical relaxation or slow trapping through a purely electrostatic effect. [25][26][27] In our device operating under dry air conditions in Fig. 3(b), such slow changes in resistance were not observed; instead, a steep, small resistance switching of 0.06% occurred, as illustrated in the inset of Fig.…”
Section: Transport Properties Under Humid Conditionsmentioning
confidence: 86%
“…Vanadium dioxide (VO 2 ) undergoes a rapid and reversible first-order displacement metal-insulator phase transition from low-temperature insulator state to high-temperature metal state at 68°C [1]. The phase transition is reversible from monoclinic to tetragonal rutile changes [2], accompanied by changes in electronic states and crystal lattices make VO 2 thin film phase changes in optical properties, electrical properties magnetic properties and etc [3], so VO 2 in the electrical switch [4] terahertz Device [5] and smart window [6] has great potential.…”
Section: Introductionmentioning
confidence: 99%